ASSOCIATION OF LIPID PROFILE ABNORMALITIES AMONG PATIENTS WITH HYPERTENSION: A RETROSPECTIVE HOSPITAL-BASED DESCRIPTIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hypertension is a major cardiovascular risk factor frequently associated with dyslipidemia, which further increases the risk of atherosclerotic cardiovascular disease. Abnormal lipid profiles among hypertensive patients contribute significantly to morbidity and mortality. This study aimed to evaluate the relationship between lipid profile abnormalities and hypertension in a hospital-based population. Methodology: This retrospective descriptive study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from March 2025 to February 2026. A total of 50 hypertensive patients were included in the study. Data regarding demographic details, blood pressure measurements, medication history, and lipid profile parameters were collected from electronic health records. Statistical analysis was performed using SPSS version 25.0. Correlation analysis, Student’s t-test, and ANOVA were used where appropriate, with p